Management and outcomes of hidden penis in children - Alireza Mirshemirani; Ahmad Khaleghnejad Tabari; Mohsen Rouzrokh; Javad Ghoroubi; Leily Mohajerzadeh; Saran Lotfollahzadeh (Pediatric Surgery Research Center of Shahid Beheshti University of Medical Sciences, 2018)
Introduction: Hidden penis may have different categories: Concealed, trapped, and buried types. The aim of this study was to evaluate the results and outcomes of repaired cases. Material and Methods: A total of 40patients (5months -12years old) underwent surgical repair for different types of hidden penis from April 2010 to December 2015 in our hospital. Multiple surgical procedures were performed for each type. Data were collected and evaluated for number of patient's, type of anomalies, surgical techniques, outcome and follow-up. Results: All forty cases underwent surgical repair. In all cases of concealed and buried penis penile degloving and penile fixation was used. In all of our cases improved function and good outcome was reported. Conclusions: Patients with hidden penis are in great psychological risks. The aim of hidden penis repair is to restore an aesthetic and functional penis which we are happy that we provided for our patients.